An artificial cytochrome P450 that hydroxylates unactivated carbons with regio- and stereoselectivity and useful catalytic turnovers - Breslow, Ronald (The National Academy of Sciences of the USA, 1997)
A catalyst has been synthesized comprising a manganese porphyrin carrying four beta-cyclodextrin groups. It catalyzes the hydroxylation of substrates of appropriate size carrying tert-butylphenyl groups that can hydrophobically bind into the cyclodextrin cavities. In one example as many as 650 catalytic turnovers are seen before the catalyst is oxidatively destroyed, and with a rate comparable to that of typical cytochrome P450 enzymes. In another example, a steroid derivative is regio- and stereoselectively hydroxylated at a single unactivated carbon atom, but more slowly and with fewer turnovers. The carbon attacked is not the most chemically reactive, and the selectivity is determined by the geometry of the catalyst-substrate complex. Nonbinding substrates are not reactive under the conditions used, and substrates with more flexible binding geometries give more than a single product.